Effect of Adding Fungal Chitosan on Sensory Properties, Microbiological Quality and Shelf life of Pan Bread - Al-Saikhan, Lugain Fahad; Al-Hassan, Ahmed Ali; Salah, Sahar Hassan; El-Sayed, Mohamed Gadallah (Journal of agricultural, environmental and veterinary sciences, 2022)
This research aims to study the effect of adding fungal chitosan as a natural preservative at different concentrations (zero, 0.5, 1 and 1.5%) on the moisture content, texture, sensory properties, and microbiological quality in pan bread during storage at room temperature (22 ± 3oC). The results show that the addition of fungal chitosan led to a significant decrease in the specific volume of the bread. It was also found that adding fungal chitosan had no significant effect on the sensory characteristics and general acceptance of the bread, except for the crust color which becomes darker in higher fungal chitosan concentrations, whereas the moisture loss rate decreased as the chitosan percentage increased. It was found that (1 and 1.5%) chitosan had the highest effect of preservation and no record of microbial growth during the storage period until five days at room temperature, which concludes that the fungal chitosan was effective as a natural preservative in the bread. In conclusion, the study results demonstrate that it is possible to prepare bread with addition up to 1% of fungal chitosan as a natural safe preservative, and it can be a successful application in bakery and particularly in bread industry as a replacement of synthetic preservatives.
Keywords: Natural preservative; anti-microbial; microbial spoilage; Bread mold; total quality